Characterization of therapeutic abortion in a level III Hospital in Peru during 12 years of experience - Guevara-Ríos, Enrique (2022)
Objective: To describe maternal characteristics and management of therapeutic abortion in women treated in a level III hospital in Peru, during 12 years of experience. Materials and Methods: Observational and retrospective study. All pregnant women who had a therapeutic interruption of pregnancy participated. The medical history of patients treated at the National Maternal Perinatal Institute of Peru, between 2009 and 2020 was reviewed. Results: 385 pregnant women were attended. The mean age was 30.4 years; 45% were nulliparous; and 51% had between 19 and 22 weeks of gestation. The causes were 7.5% due to risk of the life of the pregnant woman and 92.5% due to risk in the physical and mental health of the pregnant woman. 30% presented fetuses with multiple malformations. Uterine curettage was performed in 81%, 15.6% manual vacuum aspiration, six cases of hysterotomy. There were no cases of maternal death and complications were 5.5%. Conclusion: The cases of therapeutic interruption of pregnancy were mainly to avoid risks in the physical and mental health of the pregnant woman. The majority of the pregnant woman had fetuses with congenital malformations. The procedures performed presented a low frequency of maternal complications.